Prediction of further residual ridge resorption by a simple biochemical and radiographic evaluation: A pilot study - Mohit Kheur; Jay D Matani; Mohammad Latifi (Wolters Kluwer Medknow Publications, 2012)
Background and Objective: The success of a removable denture is measured by its retention and stability which rely on the structural integrity exhibited by the underlying residual ridge. However the residual ridge undergoes a progressive resorption, causing a reduction in its size. The multifactorial etiology of the reduction of residual ridges makes it significant for the operator to try and understand as well as to predict the rate of resorption prior to fabrication of dentures. The objective of the study was to evaluate a simple, fast and cost effective diagnostic tool to study and anticipate ridge resorption. Materials and Methods: 17 completely edentulous male patients were selected for the study. Standardized orthopantomographs were made for all the subjects and measurements were made on them. The resorption index was calculated for each patient. A random urine sample was taken from each patient to investigate the 24 hours urinary calcium-creatnine ratio. Results: A direct relation was seen between patients with lower resorption index and lower 24 hours urinary calcium-creatnine ratio. Clinically these cases had undergone a marked amount of reduction in the residual alveolar ridges with respect to the width and height. Also, a direct relation was seen when the patients presented with higher 24 hours urinary calcium-creatnine ratio and greater resorption index. These patients presented with good height and width of the residual ridges. Conclusion: Our study shows a direct relation between the resorption of the bone and the calcium-creatinine levels of the edentulous subjects. The calcium-creatnine ratio in conjunction with the resorption index can be used as a simple and cost effective diagnostic tool.